Analysis Of The Applications Of The Microalgae Botryococcus braunii In Industrial Processes - Carrascal Rivera, Derly Darleyn; Tasco Quintero, Angie Camila; Barajas Solano, Andres Fernando; García-Martínez, Janet Bibiana; Machuca Martínez, Fiderman (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Microalgae and cyanobacteria are the new biotechnological platform to produce diverse metabolites of industrial interest such as carbohydrates, proteins, lipids, carotenoids, and even fewer common metabolites such as hydrocarbons and exopolysaccharides. One of the species with the capacity to produce a broad spectrum of metabolites is Botryococcus braunii. This colonial green alga has the peculiarity of synthesizing hydrocarbons, exopolysaccharides, and other metabolites. The present contribution presents a bibliometric overview of the worldwide research on the production of B. braunii and its primary metabolites of interest for industrial processes. Data on scientific publications during the last 21 years (2000-2021) were obtained from the SCOPUS© database and filtered using a systematic search strategy. A total of 675 scientific papers focused on the isolation, production, and improvement of strains belonging to the B. braunii species were obtained from the analysis. According to the information obtained, most of the published works have focused on producing and improving hydrocarbons to produce biofuels. The major countries that have contributed the most to research on this species are the United States, Japan, China, and India; however, countries with a high concentration of biodiversity, such as Colombia, present few studies with isolated strains within the national territory. This bibliometric analysis shows the high degree of development obtained in the last 20 years to generate biotechnological platforms to obtain new raw materials for different industrial sectors.